Thermally Triggered Injectable Hydrogel Carrier System for Mesenchymal Stem Cell Delivery to Promote Intervertebral Disc Regeneration. (May 2014) - Boyes, V.; Barthrop, B.; Chiverton, N.; Cole, A.; Michael, A. R.; Breakwell, L.; Sammon, C.; Le Maitre, C. L.
Introduction: Instability of the motion segment as a result of intervertebral disc (IVD) degeneration is well known as a major cause of low back pain. Several tissue engineering and stem cell approaches have been investigated to attempt to regenerate the degenerate IVD. However, many of the proposed therapies would entail lengthy/risky operations to "implant" the tissue regeneration scaffold. Our vision is to develop a novel, injectable biomaterial delivery system which can deliver mesenchymal stem cells (MSCs) to the degenerate nucleus pulposus (NP) to stimulate regeneration, together with inhibitors of degeneration if required and provide mechanical support to the motion segment enabling regeneration to take place. Materials and Methods: Here, we investigated a novel hydrogel system, which can be maintained as a liquid ex vivo and can be injected into the IVD where body temperature triggers in situ solidification. Human MSCs were incorporated into hydrogel systems and cell viability, migration characteristics, SEM, gene expression for NP markers, and matrix production investigated to determine differentiation capacity of incorporated MSCs. Mechanical properties of hydrogel systems were determined using dynamic mechanical analysis and compared with native NP tissue. Microparticles incorporation to provide delivery of inhibitors of degeneration were also investigated. Results: Viability of MSCs was maintained within hydrogel systems for the 6 weeks investigated, where they were shown to migrate through the hydrogel system, deposit matrix within and differentiate toward NP cells with a switch in matrix gene expression from collagen type I to type II, and deposition of GAGs with immunopositivity seen for aggrecan following 4 weeks in culture. DMA analysis demonstrated hydrogel systems containing 10% hyaluronic acid displayed similar mechanical properties to native NP cells. Hydrogel systems were injected via 26-gauge needles into collagenase digested bovine caudal discs, which was maintained during loading of the bovine motion segments. In addition, microparticles were successfully incorporated into hydrogel systems in the liquid state before thermal triggered solidification. Conclusion: Here, we have developed a hydrogel system with the potential to deliver MSCs via minimally invasive injection using small bore needles which decreases the chance of inducing damage to the annulus fibrosus. Hydrogel systems were nontoxic, support MSC growth and differentiation, and show potential to provide mechanical support to the motion segment while regeneration takes place. Such a therapy combined with inhibition of degeneration could show great promise for early and mid-stages of degeneration. Disclosure of Interest None declared